Zones of radiation of impulse radiator of small electric sizes - Думин, А. Н.; Плахтий, В. А.; Вольвач, Я. С.; Думина, О. А. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2018)
The problem of the radiation of thin impulse radiator of small sizes with uniform distribution of the electric current is solved by vector potential method in time domain. The classical solution for the Hertzian dipole field is compared with the improved one, obtained earlier by taking into account a larger number of terms in the expansion of the integrand for the vector potential, and with the exact solution calculated numerically for arbitrary distances, including the extremely close distances to radiator. The radiation zones of the small source of a given nonstationary current are analyzed from the point of view of the classical definitions of zones and definitions containing the time dependence, formulated by H.F. Harmuth. New energy criterion for impulse radiation zones is proposed on the basis of H.F. Harmuth approach.